Exosome-mediated regulation of inflammatory pathway during respiratory viral disease - Hamidreza Gheitasi; Mohammad Sabbaghian; Ali Akbar Shekarchi; Amir Ali Mirmazhary; Vahdat Poortahmasebi (Virology Journal, 2024)
Abstract Viruses have developed many mechanisms by which they can stimulate or inhibit inflammation and cause various diseases, including viral respiratory diseases that kill many people every year. One of the mechanisms that viruses use to induce or inhibit inflammation is exosomes. Exosomes are small membrane nanovesicles (30–150 nm) released from cells that contain proteins, DNA, and coding and non-coding RNA species. They are a group of extracellular vesicles that cells can take up to produce and mediate communication. Intercellular effect exosomes can deliver a broad confine of biological molecules, containing nucleic acids, proteins, and lipids, to the target cell, where they can convey therapeutic or pathogenic consequences through the modulation of inflammation and immune processes. Recent research has shown that exosomes can deliver entire virus genomes or virions to distant target cells, then the delivered viruses can escape the immune system and infect cells. Adenoviruses, orthomyxoviruses, paramyxoviruses, respiratory syncytial viruses, picornaviruses, coronaviruses, and rhinoviruses are mostly related to respiratory diseases. In this article, we will first discuss the current knowledge of exosomes. We will learn about the relationship between exosomes and viral infections, and We mention the inflammations caused by viruses in the airways, the role of exosomes in them, and finally, we examine the relationship between the viruses as mentioned earlier, and the regulation of inflammatory pathways that play a role in causing the disease.